Human Rhinovirus Induced Cytokine/Chemokine Responses in Human Airway Epithelial and Immune Cells - Rajan, Devi (PLoS One, 2014)
Infections with human rhinovirus (HRV) are commonly associated with acute upper and lower respiratory tract disease and asthma exacerbations. The role that HRVs play in these diseases suggests it is important to understand host-specific or virus-specific factors that contribute to pathogenesis. Since species A HRVs are often associated with more serious HRV disease than species B HRVs, differences in immune responses they induce should inform disease pathogenesis. To identify species differences in induced responses, we evaluated 3 species A viruses, HRV 25, 31 and 36 and 3 species B viruses, HRV 4, 35 and 48 by exposing human PBMCs to HRV infected Calu-3 cells. To evaluate the potential effect of memory induced by previous HRV infection on study responses, we tested cord blood mononuclear cells that should be HRV naïve. There were HRV-associated increases (significant increase compared to mock-infected cells) for one or more HRVs for IP-10 and IL-15 that was unaffected by addition of PBMCs, for MIP-1α, MIP-1β, IFN-α, and HGF only with addition of PBMCs, and for ENA-78 only without addition of PBMCs. All three species B HRVs induced higher levels, compared to A HRVs, of MIP-1α and MIP-1β with PBMCs and ENA-78 without PBMCs. In contrast, addition of CBMCs had less effect and did not induce MIP-1α, MIP-1β, or IFN-α nor block ENA-78 production. Addition of CBMCs did, however, increase IP-10 levels for HRV 35 and HRV 36 infection. The presence of an effect with PBMCs and no effect with CBMCs for some responses suggest differences between the two types of cells possibly because of the presence of HRV memory responses in PBMCs and not CBMCs or limited response capacity for the immature CBMCs relative to PBMCs. Thus, our results indicate that different HRV strains can induce different patterns of cytokines and chemokines; some of these differences may be due to differences in memory responses induced by past HRV infections, and other differences related to virus factors that can inform disease pathogenesis.